Acute effects of heroin on emotions in heroin‐dependent patients. (11th April 2013) - Blum, Julia; Gerber, Hana; Gerhard, Urs; Schmid, Otto; Petitjean, Sylvie; Riecher‐Rössler, Anita; Wiesbeck, Gerhard A.; Borgwardt, Stefan J.; Walter, Marc
<x xml:space="preserve">Abstract</x> Background Euphoria has been described in heroin‐dependent individuals after heroin administration. However, affective disturbances and disorders are common in heroin dependence. The present study examined the acute effects of heroin on emotions in heroin‐dependent patients. Methods This randomized controlled crossover trial included 28 heroin‐dependent patients (67.9% male, n = 19) in stable heroin‐assisted treatment and 20 healthy controls. The patients were administered heroin or saline (placebo), the controls were administered saline. Data measuring mood, affects and heroin craving (BDI, AMRS, STAI, STAXI, and HCQ) were assessed before and 60 minutes after substance injection. Results Before substance injection, heroin‐dependent patients showed significantly higher levels of anxiety and depression than healthy controls (p < .0001). Heroin administration—but not placebo administration—was associated with a significant decrease in all negative emotions, including craving, and a significant increase in emotional well‐being (p < .0001), irrespective of perceived intoxication and sedation. After the experiment, the patients did not differ from healthy controls in their emotions, once they had received heroin. Conclusions Heroin dampens craving, negative emotions, and increases positive emotions. These findings indicate that heroin regulates emotions and underscore the clinical benefit of opioid substitution treatment for heroin‐dependent patients. (Am J Addict 2013;22:598–604)